Forced retirement in Ecuador´s State Universities: A privilege or condemnation to precarity? - Farfán Jaime, Rodolfo (PODIUM, 2017)
The elderly go through psychological, social and physical transition stages due to natural ageing. Working life is affected by social prejudice against the old. Discussing forced retirement brings to mind the difference between right and ethically correct. This debate includes a public ethics issue and an educational issue; teaching by inexperienced or poorly qualified teachers may affect students' academic development. This paper will look at forced retirement of Ecuadorian faculty members at the Guayaquil State University. The analysis will center on equality and ethics and will explain the issue's economical, educational and social context as well as how these decisions place university the schools and departments of the University in a state of precarity. It will also explore how forced retirement is linked with age discrimination and how it influences education, preventing students from benefitting from the experience and knowledge of older teachers.